Expression of Testicular Estrogen Receptor Alpha in Rats Exposed to Subchronic Inhalation Exposure of Transfluthrin - Kartikasari, Nanik Triana; Arsana, Putu Moda; Soeatmadji, Djoko Wahono (Universitas Brawijaya, 2020)
Endocrine Disrupting compounds (EDCs) are exogenous materials that can interfere with the functions of the endocrine system. Research has demonstrated that pyrethroid compounds affect endocrine function. Transfluthrin belongs to the pyrethroid group that is widely used. These compounds could interact with estrogen receptor α and may increase the expression of estrogen receptor α in rat testis. Aim: to determine the effect of subchronic inhaled transfluthrin exposure on the expression of estrogen receptor α (ERα). Method: we used 35 adult male Wistar rats as experimental animals, which were randomly divided into 5 groups (n=7 per group): negative control group (rats without treatment), solvent control group (rats exposed to n-hexane solvent), and three treatment groups of subchronic inhaled transfluthrin: 0.1 mg/ml (treatment 1), 0.2 mg/ml (treatment 2) and 0.4 mg/ml (treatment 3), treated for 60 days. The immunohistochemical (IHC) staining was used to assess the expression of ERα. Result: there was a tendency for an increase in ERα expression with the addition of a transfluthrin dose. ER α in negative control group, solvent control group, treatment 1 group, treatment 2 group, and treatment 3 group was 16.75 ± 5.01 %; 16.64 ± 13.00 %; 19.31 ± 6.52 %; 25.63 ± 7.08 %, and 28.79 ± 20.31 %; p>0.05, respectively. There was a weak positive correlation between the dose of transfluthrin with ERα expression (r = 0.38, p = 0.025). Conclusion: subchronic inhalation exposure of transfluthrin in rats showed a tendency to increased the expression of ERα (dose-dependent). There is a weak positive correlation between the dose of transfluthrin with ERα expression.